Child physical abuse: awareness and practices of medical and dental doctors in Pakistan - Hafiz Muhammad Ali Khan; Naveed Mansoori; Muhammad Hamza Sohail; Muhammad Ajwad Humayun; Anam Liaquat; Syed Muhammad Mubeen (Journal of the Pakistan Medical Association, 2021)
Objectives: To determine the awareness and practices of medical and dental doctors in detecting and reporting suspected cases of child physical abuse. Methods: A cross-sectional study was done from November 2017 to June 2018 among medical and dental doctors practising in public and private hospitals across Pakistan. Using convienence sampling technique a structured questionnaire was administered. The questionnaire addresses knowledge of the social indicators of child physical abuse, response to child physical abuse, and actions taken by doctors when they believe a child abuse case has been decided. Descriptive analysis was done, and Chi-square test was used for the association of knowledge about child physical abuse and sex. P-value < 0.05 was considered as statistically significant. Results: Out of total 575 doctors, 347 (60.3%) were males and 446 (77.6%) work in private hospitals. The majority of doctors 384 (66.8%) had <10 years of experience and only 99(17.2%) had received formal training of child abuse. A fifth of doctors agreed to tell someone immediately after being physically abused for social indicators of child physical abuse and considered statistically significant between the sexes (P<0.05). Most doctors 450(78.3%) strongly agreed on the value of identifying and documenting child physical abuse while 563(97.9%) doctors did not take any action to suspect a child abuse case. Conclusion: The study revealed sufficient knowledge among doctors about child physical abuse. Although the doctors had a positive attitude regarding child physical abuse, a large proportion remain silent on its suspicion. Keywords: Child, Physical abuse, Physicians, Continuous...